Main circulating CD8+ T cell subsets in patients with systemic lupus erythematosus - S. S. Benevolenskaya; I. V. Kudriavtsev; M. K. Serebriakova; A. A. Rubinstein; E. S. Kuvardin; I. N. Grigor’yeva; D. B. Aliev; D. B. Zammoeva; D. B. Motorin; A. S. Golovkin; O. V. Kalinina; S. V. Lapin; et al. (Научно-практическая ревматология)
Relevance. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by loss of immune tolerance and sustained production of autoantibodies.The aim of the study – to compare composition of peripheral blood cytotoxic CD8+ T lymphocytes (Tc) subsets and assess the clinical significance of them in systemic lupus erythematosus. Materials and methods. A total of 35 SLE patients and 49 healthy volunteers were included in the study. Phenotyping of peripheral blood T cell subpopulations was carried out by means of flow cytometry. T lymphocytes were determined using CD3+, CD4+, CD8+ antibodies. Tc were identified by using CD45RA and CD62L antibodies. Also the expression of chemokine receptors (CCR4, CCR6, CXCR3 and CXCR5) on Tc cells was assessed and the main Tc subpopulations were determined: Type 1 (Tc1), type 2 (Tc2), type 17 (Tc17), type 17/1 (Tc17.1), type 17/22 (Tc17.22) cytotoxic cells and T follicular cytotoxic cells (Tfc).Results. The absolute and relative number of Tc was significantly higher in the group of patients with SLE compared with the control group. Additionally, there was a significant decrease in the relative number of Tc1, Tc 17.1 and Tfc1 and a significant increase in the relative number of Tc2, Tfc 17 and Tfc17.1 within the SLE group when compared to the control group. There were significant positive correlationfor Tc1 and levels of C3 and C4 complement components (r=0.404, p<0.05).Conclusions. The absolute and relative number of peripheral blood Tc subsets is altered in SLE patients compared with the control group. It was found that patients with SLE contained increased number of Tc2 cells, which seems to be associated with markers of disease activity. These results demonstrate a prominent pathological role of Tc2 in SLE. While Tc1, Tc17, Tc17.1, Tfc subsets probably have regulatory functions